RecurIndex assay as an aid for adjuvant chemotherapy decisions in HR-positive HER2-negative breast cancer patients - Wang, Haibo; Ma, Li; Zhang, Yanan; Wang, Ouchen; Wei, Zhimin; Xie, Xiaohong; Zha, Xiaoming; Zeng, Jian; Lv, Qing; Ren, Yu; Wang, Huimin; Du, Furong; et al. (Frontiers in Oncology, 2022)
Adjuvant chemotherapy is a major adjuvant treatment modality for hormonal receptor (HR)-positive and HER2-negative early breast cancer, but only 2%-20% of patients derive practical benefits. How to balance its potential benefits and risks becomes a challenging clinical problem. The purpose of this study was to assess whether RecurIndex assay could serve as an aid for adjuvant chemotherapy decisions in Chinese patients with HR-positive HER2-negative early breast cancer. The tissue samples of pT1-2N0 HR-positive HER2-negative breast cancer from multiple centers were detected using RecurIndex assay, based on which the patients were assigned into low- and high-risk groups. The survival outcomes of low- and high-risk patients including those with and without adjuvant chemotherapy were compared, and the risk factors for recurrence and metastasis were identified. Totally 445 patients were eligible for analysis. By contrast to high-risk patients, low-risk patients represented better 7-year recurrence-free survival (RFS), distant recurrence-free survival (DRFS) and local recurrence-free survival (LRFS) rates. For low-risk patients, no significant differences were shown between those with and without adjuvant chemotherapy in 7-year RFS, DRFS and LRFS rates. These differences were also inapparent between high-risk patients with and without adjuvant chemotherapy. The multivariate model revealed high-risk patients had a significantly elevated risk of recurrence and metastasis than those at low risk. Overall, HR-positive HER2-negative early breast cancer patients at low risk stratified by RecurIndex assay might be exempt from adjuvant chemotherapy. Whether adjuvant chemotherapy may derive survival benefits for high-risk patients still needs larger cohorts to verify.